1974
DOI: 10.1111/j.1476-5381.1974.tb09727.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pithing and of Nerve Stimulation on the Depletion of Noradrenaline by Reserpine in the Rat Anococcygeus Muscle and Vas Deferens

Abstract: 1The depletion of noradrenaline (NA) in the rat anococcygeus muscle and vas deferens by reserpine and the effect on this of the abolition of nerve activity by pithing and reinforcement of nerve activity by stimulation of the spinal cord outflows has been studied. 2 NA depletion of the anococcygeus and vas deferens measured 24 h after reserpine was similar and was related to dose. The heart was depleted faster than the two smooth muscle tissues. 3 In the absence of reserpine neither abolition of nerve activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

1974
1974
1986
1986

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 22 publications
(25 reference statements)
2
42
0
Order By: Relevance
“…The effect mine. Using reserpine alone, Sj6strand & Swedin one was identical with (1968) and Gillespie & McGrath (1974) showed that o L it was more difficult to deplete noradrenaline in the vas deferens than in the heart though doses of reserpine higher than 1.0 mg/kg were usually effective in both tissues. Sjostrand & Swedin (1968) thought that this could be due to the properties of the short adrenergic neurones which supply the vas deferens, or less likely to poor circulation to the organ.…”
Section: Dicussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The effect mine. Using reserpine alone, Sj6strand & Swedin one was identical with (1968) and Gillespie & McGrath (1974) showed that o L it was more difficult to deplete noradrenaline in the vas deferens than in the heart though doses of reserpine higher than 1.0 mg/kg were usually effective in both tissues. Sjostrand & Swedin (1968) thought that this could be due to the properties of the short adrenergic neurones which supply the vas deferens, or less likely to poor circulation to the organ.…”
Section: Dicussionmentioning
confidence: 85%
“…Sjostrand & Swedin (1968) thought that this could be due to the properties of the short adrenergic neurones which supply the vas deferens, or less likely to poor circulation to the organ. Gillespie & McGrath (1974) showed that it was more likely to be due to much less frequent stimulation of the vas than the heart in the intact reserpine-treated animals, since stimulation of the sympathetic nerves to the vas, after reserpine treatment increased the depleting effect of the drug. Therefore, to ensure that the maximum possible depletion of the noradrenaline in the vas was obtained in these experiments, a high dose of reserpine was used and the extent of the depletion of noradrenaline in the heart was measured for comparison.…”
Section: Dicussionmentioning
confidence: 99%
“…This schedule reduces the noradrenaline content of the rat vas deferens by over 98% (Gillespie & McGrath, 1974).…”
Section: Methodsmentioning
confidence: 99%
“…Following reserpine, no 'twitch' is present and the response is monophasic. Previously the effect of reserpine could not be clearly interpreted since it was thought that the 'twitch' was 'nonadrenergic' (Ambache & Zar, 1971), yet it was reduced by reserpine (Gillespie & McGrath, 1974). …”
Section: Trains Of Stimulimentioning
confidence: 99%
“…The muscle has a dense adrenergic motor innervation, but there is no evidence of cholinergic nerves; it does, however, possess a powerful inhibitory innervation mediated by an unknown transmitter (Gillespie, 1972;Gillespie & McGrath, 1972).…”
Section: Introductionmentioning
confidence: 99%